Preparation method of water-soluble bio-based aramid fiber / ceramic coated battery diaphragm

By mixing water-soluble bio-based aramid with ceramic material and aluminum sol, aqueous slurry is prepared and coated on the battery separator, the problems of increased breathability, poor adhesion and insufficient wettability of the separator in the prior art are solved, and the high temperature tolerance, wetting and adhesion are improved, and are suitable for a variety of battery types.

CN119890610AActive Publication Date: 2025-04-25UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202510378962.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

In the existing aramid-coated diaphragm technology, there are problems such as large increase in the permeability of the coated diaphragm, poor adhesion between the composite coating and the base film, and insufficient wettability. The bio-based aramid particles are incompatible and prone to agglomeration in the slurry.

Method used

Water-soluble bioaramid is mixed with ceramic material, aluminum sol and additives to obtain an aqueous slurry. The aqueous slurry is coated on one or both sides of the base film through the coating process to form a water-soluble bioaramid/ceramic coated battery separator.

Benefits of technology

It improves the high temperature tolerance of the coated separator, the wetting properties of the electrolyte and the adhesiveness of the coating, reduces the phenomenon of plugging of the coating, and improves the breathability of the separator. It is suitable for lithium-ion batteries, sodium-ion batteries, semi-solid batteries, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890610A_ABST
    Figure CN119890610A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of compositions of high-molecular compounds for battery diaphragms, and discloses a preparation method of a water-soluble bio-based aramid / ceramic coated battery diaphragm, which comprises the following steps: mixing water-soluble bio-based aramid with a ceramic material, aluminum sol and an auxiliary agent through a coating process to prepare water-based slurry, and coating one or two surfaces of a base membrane with the water-based slurry, thereby obtaining the water-soluble bio-based aramid / ceramic coated battery diaphragm. And obtaining the required diaphragm. The water-soluble bio-based aramid fiber component is added into the coating slurry, so that the high-temperature tolerance, electrolyte wettability and coating binding power of the diaphragm can be improved, and the aluminum sol binder component is added to be matched with the water-soluble bio-based aramid fiber for use, so that the coating hole blocking phenomenon can be relieved, and the air permeability of the diaphragm can be improved; the diaphragm is suitable for lithium ion batteries, sodium ion batteries, semi-solid batteries and the like, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of compositions of polymer compounds for battery separators, and in particular to a method for preparing a water-soluble bio-based aramid / ceramic coated battery separator. Background Art

[0002] As lithium-ion batteries develop towards high energy density, high capacity, and high reliability, traditional polyolefin separators are difficult to meet the demand due to poor heat resistance and insufficient affinity with the electrolyte. To this end, academia and industry have developed separator coating technology. A common method is to coat an inorganic ceramic coating (such as Al2O3, SiO2, or boehmite) on the surface of a polyolefin base membrane. Although it improves high temperature resistance and liquid affinity, there are problems such as poor bonding between ceramic particles and the base membrane and easy falling off. Although adding a binder can enhance the bonding force, it is easy to clog the diaphragm pores, resulting in decreased air permeability. Another option is to apply a polyvinylidene fluoride (PVDF) organic coating, but its hydrophobicity depends on an oily coating process, which has problems such as large amounts of organic solvents, high costs, and environmental pollution.

[0003] In recent years, petroleum-based aramid (such as para-aramid PPTA) has been introduced into the field of diaphragm coatings due to its high strength, high modulus and excellent thermal stability (decomposition temperature>500℃). Studies have shown that aramid-coated diaphragms can still maintain structural stability at high temperatures, significantly reduce thermal shrinkage (shrinkage <5% at 180℃), and can improve the interfacial bonding between the coating and the base film through modification with silane coupling agents, avoiding the problem of powder loss in ceramic coatings. However, the promotion of petroleum-based aramid is restricted by multiple factors: the synthesis of its production monomers (such as terephthaloyl chloride) depends on petroleum raw materials; aramid fibers are difficult to crush and disperse due to their high strength and high modulus properties, and require special equipment (such as PFI refiners) for processing; aramid has a smooth surface and lacks active groups, and the interfacial bonding with the binder depends on physical effects, and interfacial peeling is prone to occur during long-term circulation.

[0004] In order to reduce dependence on petroleum resources, bio-based aramid (biomass-derived monomers replacing petroleum-based raw materials) has been introduced into the research of the diaphragm coating industry. For example, aramid with bio-based p-phenylenediamine or furandicarboxylic acid as monomers is green and degradable. Preliminary experiments show that bio-based aramid coatings are close to petroleum-based aramid in terms of heat resistance (decomposition temperature>400°C) and mechanical strength, and have richer surface polar groups and better compatibility with electrolytes. After coating, the chemical bonding with the base membrane can be enhanced. However, the water-based bio-based aramid currently used is mainly composed of fibers and particles. The state after dispersion in water is unstable, and a uniform slurry cannot be formed after standing. Summary of the invention

[0005] In order to solve the problems existing in the existing aramid coated membrane technology, such as large air permeability increment of the coated membrane, poor adhesion between the composite coating and the base membrane, insufficient wettability, and incompatibility and easy agglomeration of the existing bio-based aramid particles in the slurry, the present invention proposes a method for preparing a water-soluble bio-based aramid / ceramic coated battery membrane.

[0006] In order to achieve the purpose, the present invention adopts the following technical scheme: The present invention first provides a method for preparing a water-soluble bio-based aramid / ceramic coated battery separator, which comprises the following steps: mixing water-soluble bio-based aramid with ceramic materials, aluminum sol and additives to prepare an aqueous slurry, and coating the aqueous slurry on one or both sides of a base film through a coating process to obtain a water-soluble bio-based aramid / ceramic coated battery separator.

[0007] Furthermore, based on dry weight, the mass percentage of each raw material in the aqueous slurry is: 8-11 wt% of water-soluble bio-based aramid, 85-87 wt% of ceramic material, 0.1-0.5 wt% of dispersant, 1-4 wt% of aluminum sol, and 0.1-1.0 wt% of wetting agent.

[0008] Preferably, the water-soluble bio-based aramid is prepared with reference to patent CN118667151A: by introducing a polyamic acid segment into the main chain of the bio-based aramid containing a furan ring, and then salifying to form a strong hydrophilic segment, a water-soluble bio-based aramid is obtained, and a water-based coating of aramid is achieved. The prepared bio-based aramid material has good water solubility and coating adhesion, and can be compounded with aluminum sol to play a synergistic role and act as an adhesive in the battery separator formulation. In addition, the unique polar groups of the bio-based aramid material have similar polarity and structure to the main organic solvent molecules of the electrolyte, and will interact more strongly with the electrolyte and have a better wetting effect. Therefore, the water-soluble bio-based aramid / ceramic coated battery separator prepared by mixing with ceramic particles and the like exhibits excellent mechanical strength, thermal shrinkage stability and electrolyte wetting properties.

[0009] Preferably, the base film is at least one of a PP membrane, a PE membrane, a non-woven fabric and a fiber membrane.

[0010] Preferably, the ceramic material is at least one of boehmite, alumina, silicon oxide and titanium oxide, and most preferably boehmite; the particle size of the ceramic material is 100-1000 nm.

[0011] Preferably, the dispersant is at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, acrylate and polyurethane, and sodium carboxymethyl cellulose is most preferred.

[0012] Preferably, the wetting agent includes at least one of polyether-modified dimethylsiloxane, polyoxyethylene ether, sodium dodecyl sulfonate, polyether-modified siloxane and modified succinic acid, and polyoxyethylene ether is most preferred.

[0013] The chemical formula of the aluminum sol binder is a(Al2O3·nH2O)·bHx·cH2O, wherein: Al2O3·nH2O is hydrated aluminum oxide, H x is a peptizing agent, coefficient: b<a, c, n. Water-soluble bio-based aramid contains abundant polar groups (such as hydroxyl, amino, carboxyl, etc.), which can react with aluminum ions (Al 3+ ) or hydroxyaluminum complexes (such as [Al(OH)2(H2O)4] + ) to form a dynamic cross-linked network. The Lewis acidity of aluminum ions can bind to the carboxyl groups of aramid through chelation to enhance the interfacial bonding force. At the same time, hydrogen bonds are formed between the hydroxyl groups of aluminum sol and aramid to further stabilize the composite structure. Secondly, aluminum sol can be embedded in the three-dimensional network of bio-based aramid as a nanofiller to form an "organic-inorganic" bicontinuous structure. The nanoparticles of aluminum sol fill the pores of aramid through in-situ cross-linking to form a hierarchical pore structure, which not only improves the mechanical strength but also retains the liquid permeability of the material.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: The water-soluble bio-based aramid / ceramic coated battery diaphragm prepared by the present invention has uniform pores, an air permeability of 100-200 s / 100cc, an electrolyte (EC:PC:DEC=1:1:1+1 M LiPF6) wetting rate of 80-100 mm / 60s, a heat shrinkage of <2% in MD direction and <2% in TD direction at 150°C for 1 h, and a coating peel strength of 110-140 N / m. The present invention adds a water-soluble bio-based aramid component to the coating slurry to improve the high temperature tolerance, electrolyte wettability and coating adhesion of the coated diaphragm, and adds an aluminum sol binder component and uses it together with the water-soluble bio-based aramid to reduce the coating pore blocking phenomenon and improve the diaphragm air permeability. The diaphragm of the present invention is suitable for lithium ion batteries, sodium ion batteries, semi-solid batteries, etc., and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1This is the SEM surface image of the water-soluble bio-based aramid / ceramic coated battery separator prepared in Example 1. DETAILED DESCRIPTION

[0017] In order to explain the present invention more clearly, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Example 1 This embodiment provides a method for preparing a water-soluble bio-based aramid fiber / ceramic coated battery separator, which specifically includes the following steps: Step 1: Use a balance to weigh 21.43 kg of boehmite aqueous slurry (solid content 43%, particle size D 50 =0.34 μm), 22.26 kg water-soluble bio-aramid (5% solid content), 1.391 kg aluminum sol (20% solid content), 1.21 kg sodium carboxymethyl cellulose dispersant (1.7% solid content), 0.05 kg polyoxyethylene ether wetting agent (100% solid content) in a stirring tank (the dry weight ratio of aramid: aluminum sol is 4:1). The stirring time for each addition is controlled to be 20 min, the revolution speed is 25 rpm, the rotation speed is 2000 rpm, and the stirring temperature is 25°C, so that it is fully dispersed to form a milky white slurry without impurities.

[0019] Step 2: Coating was performed on an online rod coater with a gap of 1-3 μm, and a 7 μm commercial polyethylene separator was used as the coating base film. The film was then placed in a blast oven at 60°C and dried for 10 minutes to obtain a water-soluble bio-based aramid / ceramic coated battery separator.

[0020] Example 2 The preparation method and operating conditions of the coated diaphragm in this embodiment are basically the same as those in Example 1, with the only difference being that the mass of the added water-soluble bio-based aramid (solid content of 5%) is 20.87 kg, and the mass of the aluminum sol (solid content of 20%) is 1.74 kg (the dry weight ratio of aramid:aluminum sol is 3:1).

[0021] Example 3 The preparation method and operating conditions of the coated diaphragm in this embodiment are basically the same as those in Example 1, with the only difference being that the mass of the added water-soluble bio-based aramid (solid content of 5%) is 23.18 kg, and the mass of the aluminum sol (solid content of 20%) is 1.16 kg (the dry weight ratio of aramid:aluminum sol is 5:1).

[0022] Example 4 The preparation method and operating conditions of the coated diaphragm in this embodiment are basically the same as those in Example 1, with the only difference being that the mass of the added water-soluble bio-based aramid (solid content of 5%) is 23.85 kg, and the mass of the aluminum sol (solid content of 20%) is 0.99 kg (the dry weight ratio of aramid:aluminum sol is 6:1).

[0023] Comparative Example 1 The preparation method and operating conditions of the coated diaphragm in this comparative example are basically the same as those in Example 1, except that 1.391 kg of aluminum sol (solid content is 20%) is replaced by 1.391 kg of styrene-butadiene latex binder (solid content is 20%, and the dry weight ratio of aramid:styrene-butadiene latex is 4:1).

[0024] Comparative Example 2 The preparation method and operating conditions of the coated diaphragm in this comparative example are basically the same as those in Example 1, except that 1.391 kg of aluminum sol (solid content of 20%) is replaced by 1.391 kg of polyacrylate adhesive (solid content of 20%, dry weight ratio of aramid:polyacrylate is 4:1).

[0025] Comparative Example 3 The preparation method and operating conditions of the coated diaphragm in this comparative example are basically the same as those in Example 1, except that 1.391 kg of aluminum sol (solid content is 20%) is replaced by 1.391 kg of polyacrylonitrile binder (solid content is 20%, and the dry weight ratio of aramid:polyacrylonitrile is 4:1).

[0026] Comparative Example 4 The preparation method and operating conditions of the coated diaphragm in this comparative example are basically the same as those in Example 1, except that the addition amount of the aluminum sol component is 0.

[0027] Comparative Example 5 The preparation method and operating conditions of the coated diaphragm in this comparative example are basically the same as those in Example 1, with the only difference being that the mass of the added water-soluble bio-based aramid (solid content of 5%) is 18.54 kg, and the mass of the aluminum sol (solid content of 20%) is 2.32 kg (the dry weight ratio of aramid:aluminum sol is 2:1).

[0028] Comparative Example 6 The preparation method and operating conditions of the coated diaphragm in this comparative example are basically the same as those in Example 1, except that the mass of the added water-soluble bio-based aramid (solid content is 5%) is 9.27 kg, and the mass of the aluminum sol (solid content is 20%) is 4.64 kg (the dry weight ratio of aramid:aluminum sol is 1:2).

[0029] The diaphragms obtained in each embodiment and comparative example were tested, and the specific testing instruments and methods are shown in Table 1: Table 1

[0030] The performance comparison of the diaphragms obtained in the embodiments and the comparative examples is shown in Table 2.

[0031] Table 2

[0032] From the data in Table 2, we can see that: Compared with Comparative Examples 1-3 using other types of adhesives, the air permeability of the membranes of Examples 1-4 increased less than that of the PE-based membrane, and the pore blocking phenomenon was not obvious. It can be seen that compared with other types of adhesives, the use of aluminum sol in combination with water-soluble bio-based aramid can effectively reduce the air permeability increment of the coated membrane. In addition, compared with other types of adhesives, the membranes obtained in Examples 1-4 have lower thermal shrinkage and better heat resistance.

[0033] Compared with Comparative Example 6, the peel strength between the diaphragm obtained in Examples 1-4 and the coating is high, and the coating is not easy to fall off, which indicates that too high a proportion of aluminum sol addition will weaken the bonding force between the coating and the base film.

[0034] By comparing the 150°C / 1h heat shrinkage of the separators obtained in Examples 1-4 and Comparative Examples 4-6, it can be seen that the heat shrinkage of the separators obtained in Examples 1-4 is less than 5%, which is beneficial to the safety of lithium-ion batteries at high temperatures. Combining Comparative Examples 4 and 6, it can be seen that the water-soluble bio-based aramid itself has a certain bonding force with the base film.

[0035] All numerical specifications of the present invention (such as temperature, time, concentration and weight, etc., including ranges of each thereof) are generally approximate values ​​that can be appropriately changed by increments of 0.1 or 1.0 (+) or (-). All numerical specifications can be understood as being preceded by the term "about".

[0036] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be made by other technicians in this field without inventive work falls within the protection scope of the present invention.

Claims

1. A method for preparing a water-soluble bio-based aramid / ceramic coated battery separator, characterized in that: The water-soluble bio-based aramid fiber is mixed with ceramic material, aluminum sol and additives to prepare an aqueous slurry; the aqueous slurry is coated on one or both sides of a base film through a coating process to obtain a water-soluble bio-based aramid fiber / ceramic coated battery separator.

2. The method for preparing a water-soluble bio-based aramid / ceramic coated battery separator according to claim 1, characterized in that: Based on dry weight, the mass percentages of the raw materials in the aqueous slurry are: 8-11 wt% of water-soluble bio-based aramid, 85-87 wt% of ceramic material, 0.1-0.5 wt% of dispersant, 1-4 wt% of aluminum sol, and 0.1-1.0 wt% of wetting agent.

3. The method for preparing a water-soluble bio-based aramid / ceramic coated battery separator according to claim 1, characterized in that: The base film is at least one of a PP membrane, a PE membrane, a non-woven fabric and a fiber membrane.

4. The method for preparing a water-soluble bio-based aramid / ceramic coated battery separator according to claim 1 or 2, characterized in that: The ceramic material is at least one of boehmite, aluminum oxide, silicon oxide and titanium oxide; the particle size of the ceramic material is 100-1000nm.

5. The method for preparing a water-soluble bio-based aramid / ceramic coated battery separator according to claim 2, characterized in that: The dispersant is at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, acrylate and polyurethane.

6. The method for preparing a water-soluble bio-based aramid / ceramic coated battery separator according to claim 2, characterized in that: The wetting agent includes at least one of polyether-modified dimethylsiloxane, polyoxyethylene ether, sodium dodecyl sulfonate, polyether-modified siloxane and modified succinic acid.

7. A water-soluble bio-based aramid / ceramic coated battery separator prepared by the preparation method according to any one of claims 1 to 6.

8. A battery, characterized in that: The battery comprising the separator according to claim 7 is a primary battery or a secondary battery.

Citation Information

Patent Citations

  • Ceramic Membrane Having Support Materials Comprising Polyaramide Fibers And Method For Producing Said Membranes

    CN102481526A

  • Preparation method of composite membrane

    CN104241569A

  • Electrode assembly using two-stage ceramic coating separator and lithium ion secondary battery comprising same

    CN115799764A

  • Composite diaphragm as well as preparation method and application thereof

    CN116487819A

  • Diaphragm, electrochemical device and electronic device

    CN116565458A

Cited By

  • High-strength water-soluble aramid fiber coating diaphragm and preparation method thereof

    CN120581834A